2022
DOI: 10.1177/10659129211072558
|View full text |Cite
|
Sign up to set email alerts
|

Value Disagreement and Partisan Sorting in the American Mass Public

Abstract: Decades ago, research described American political culture in terms of consensus. Contemporary research, however, reaches opposite conclusions, arguing that the “culture war” that now defines American politics stems from value disagreements among partisan and ideological groups. What factors are at work in this transition from consensus to dissensus? This manuscript pulls from two literatures—one on American core political values and another on partisan-ideological sorting and affective polarization—and argues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…And because values are thought to be stable (Searing et al, 2019), they can help produce consistent political behaviors among citizens who do not engage in ideological thinking (Zaller, 1992;Feldman, 2003). Indeed, many studies have shown values are associated with political attitudes, identities, and behaviors (e.g., Feldman, 1988;Jacoby, 2006Jacoby, , 2014Schwartz et al, 2010;Goren, 2012;Evans and Neundorf, 2020;Lupton et al, 2020;Ciuk 2022;Ollerenshaw and Johnston, 2022). Enders and Lupton (2021) extend this values literature, concluding that affective polarization between 1992 and 1996 increased as Americans made reasonable judgements about the values represented by parties, ideological groups, and presidential candidates.…”
Section: Discussionmentioning
confidence: 99%
“…And because values are thought to be stable (Searing et al, 2019), they can help produce consistent political behaviors among citizens who do not engage in ideological thinking (Zaller, 1992;Feldman, 2003). Indeed, many studies have shown values are associated with political attitudes, identities, and behaviors (e.g., Feldman, 1988;Jacoby, 2006Jacoby, , 2014Schwartz et al, 2010;Goren, 2012;Evans and Neundorf, 2020;Lupton et al, 2020;Ciuk 2022;Ollerenshaw and Johnston, 2022). Enders and Lupton (2021) extend this values literature, concluding that affective polarization between 1992 and 1996 increased as Americans made reasonable judgements about the values represented by parties, ideological groups, and presidential candidates.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of accountability for nasty rhetoric mirrors other, recent work on norm violations more generally, which finds that the public is blasé when confronted with norm violations. In a deeply divided public, where values are contested (Ciuk 2023) and partisanship structures even nonpolitical behaviors (Iyengar, Westwood, and Llekes 2019), punishment for wrongdoing is rarely guaranteed. Elites and ordinary citizens have symbolic and material incentives to downplay wrongdoing in the name of partisan self‐interest.…”
Section: Civility Norms In Politicsmentioning
confidence: 99%
“…Similarly, political ideology is measured on an ordinal scale from liberal to conservative. We omit a measure of party identity due to the strong overlaps between party and ideology and the problems of applying party labels outside of non-white populations (Mason, 2015; Ciuk, 2023; Jefferson, 2020).…”
Section: Data and Variables Of Interestmentioning
confidence: 99%